Hypertension screening across different age groups in Indian adults: Evidence from nationally representative cross-sectional data - Prakash Mathiyalagen; Anand Rajagopal; Kavita Vasudevan; Sridevi Gnanasekaran; Sharath Burugina Nagaraja; Jayanta Bora; Sonu Goel (PLoS ONE, 2025)
Background Hypertension is a significant public health concern globally and in India, contributing substantially to the burden of cardiovascular diseases. Early detection through appropriate screening practices is critical to mitigating its long-term impact. However, there is limited evidence on age-specific screening practices for hypertension in the Indian population. This study aims to assess hypertension screening practices across different age groups and identify associated socio-demographic, behavioral, and physiological factors to inform effective public health strategies. Methods A cross-sectional study was conducted using data from the fifth National Family Health Survey (NFHS-5), which included 1,01,839 men and 7,24,115 women aged 15 years and above. Hypertension was defined based on systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure (DBP) ≥90 mmHg. Multivariate logistic regression was used to analyze associations between hypertension and various socio-demographic and behavioral factors. Receiver Operating Characteristic (ROC) analysis determined the optimal age for initiating hypertension screening. Results The prevalence of hypertension increased linearly with age, with a significant rise observed in the 35-39 years age group. Factors significantly associated with hypertension included marital status, religion, education, wealth index, alcohol consumption, and waist-hip ratio. ROC analysis identified 35 years as the optimal age for initiating routine hypertension screening in both men and women. Screening in this age group showed balanced sensitivity and specificity for early detection of hypertension. Conclusions This study highlights the need to revise hypertension screening policies in India, recommending initiation at 35 years to improve early detection and management. Addressing socio-demographic and lifestyle determinants through targeted interventions is critical to achieving national hypertension control goals.